Host Plant Preferences of Butterflies (Lepidoptera: Rhopalocera) in Sriwijaya University Campus of Indralaya, South Sumatra - APRILLIA, INA; LAMIN, SYAFRINA; SETIAWAN, DONI (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2024)
Hostplants are important for butterflies becaue the plants are where they lay their eggs and catterpilars will to eat after. A study to about butterflies diversity and their host plant preferences has been carried out in July-September 2014 in Sriwijaya University Campus of Indralaya, South Sumatra. This research was to determine the preferences and identify the various species larval host plants and nectar sources of butterflies in Sriwijaya University Campus of Indralaya. We applied sampling points using purposive sampling method. Our findings suggest that there were 8 larval host plant family Achantaceae, Annonaceae, Cleomaceae, Fabaceae, Lauraceae, Malvaceae, Passifloraceae and Rutaceae. The nectar host plants are 8 Family of plants consisting of Achantaceae, Asteraceae, Loganiaceae, Malvaceae, Oxalidaceae, Passifloraceae, Rubiaceae and Verbenaceae. The highest percentage of host larvae in Family Rutaceae and Achantaceae of 23% and a low of Malvaceae by 7%. The highest nectar host is Family Verbenaceae by 32% and the lowest is Family Loganiaceae with 2%.